Metaphorical representation of anthropomorphic concepts in British and American fairy tales - Yesypenko, Nadia; Pavlovych, Tetiana; Migorian, Olga; Bloshchynskyi, Igor; Mysechko, Olha (Journal of Language and Linguistic Studies, 2022)
The article reveals the results of the research of the metaphorical fragment of anthropomorphic concepts in the fairy tales of the USA and Great Britain from the perspective of conceptual modeling. The conducted research allows asserting that the models involved in the process of the anthropomorphic metaphorical conceptualization in the framework of the national worldview of the British and the Americans are similar. The comparative analysis of the metaphorical fragments of American and British fairy tales revealed a variety of image schemas, with MOTION in SPACE and EXISTENCE being dominant to assign qualities of CREATURE and HUMAN to inanimate entities. Metaphtonymies, which prevail in American fairy tales, elucidate the nomination PART of the BODY/FUNCTIONS of the BODY of the CREATURE that has a kinesthetic contact with the heroes of the fairy tales. In fairy tales, a non-living entity takes on characteristics that generally are ascribed to a human, which means ontological metaphors depend on beliefs that the British and the Americans may share about the nature and features of the entities that are anthropomorphized. The research proved that anthropomorphic metaphors in fairy tales are created by explicit metaphorical similes and personification. The frequent EMOTION metaphorical similes represent a conception of emotions as a phenomenon of nature like a ‘blast of wind’, ‘hot salt water’ or ‘poisonous flower’. Emotions in American and British fairy tales are conceptualized metaphorically as objects or substances that are easy to comprehend. The same tendency to assign anthropomorphic features is observed in the instances of personification. In fairy tales personification extends ontological metaphors.
Keywords: anthropomorphic feature; ontological concept; source-domain; target-domain; conceptual metaphor; image schema; metaphorical modeling